Effect of Khat Chewing on Helicobacter pylori Infection Treatment Outcome Following Standard Triple Therapy: A Single-Center Study in Sana'a City, Yemen - Hind F. A. Al-Sanabani; Butheina A. A. Al-Amrani (University of Science and Technology, Sana’a, Yemen, 2025)
Background: Helicobacter pylori infection is a well-established risk factor for gastrointestinal diseases, affecting approximately half of the global population, with higher prevalence rates in developing countries. Chewing khat is a widespread habit in Yemen and has been suggested to affect the outcome of standard triple therapy (STT) for H. pylori infection. Therefore, this study aimed to assess the effect of khat chewing on H. pylori infection treatment outcome after STT at a single center in Sana'a city, Yemen. Methods: A single-arm longitudinal study was conducted among 123 H. pylori-infected patients at the internal medicine outpatient clinics of the Modern European Hospital in Sana'a, Yemen, from March to September 2024. Infection was confirmed using stool antigen testing, and all participants received STT twice daily for 14 days. Stool samples were collected at baseline and four weeks after completing STT to assess the cure rate of H. pylori infection. Additionally, the association between khat chewing and the outcome of STT for eradicating H. pylori infection was analyzed using the chi-square test, with a significance level set at P < 0.05. Results: Four weeks after completing STT, the overall cure rate was 65.9% (81/123). The cure rates of H. pylori infection with STT were 63.5% (40/63) among khat chewers and 68.3% (41/60) among khat non-chewers. However, no statistically significant association was found between khat chewing and the outcome of STT for H. pylori infection (P = 0.571). Conclusion: Approximately two-thirds of H. pylori infections among Yemeni patients can be successfully eradicated using STT. However, its effectiveness needs to be evaluated across different regions of Yemen. Furthermore, khat chewing appears to have no impact on the outcome of STT, highlighting the need for further studies to explore other factors that may influence the success of STT in treating H. pylori infection.